Use of Recombinant Adenovirus Vectored Consensus IFN-α to Avert Severe Arenavirus Infection - Gowen, Brian B. (Public Library of Science, 2011)
Several arenaviruses can cause viral hemorrhagic fever, a severe disease with case-fatality rates in hospitalized individuals ranging from 15-30%. Because of limited prophylaxis and treatment options, new medical countermeasures are needed for these viruses classified by the National Institutes of Allergy and Infectious Diseases (NIAID) as top priority biodefense Category A pathogens. Recombinant consensus interferon alpha (cIFN-α) is a licensed protein with broad clinical appeal. However, while cIFN-α has great therapeutic value, its utility for biodefense applications is hindered by its short in vivo half-life, mode and frequency of administration, and costly production. To address these limitations, we describe the use of DEF201, a replication-deficient adenovirus vector that drives the expression of cIFN-α, for pre- and post-exposure prophylaxis of acute arenaviral infection modeled in hamsters. Intranasal administration of DEF201 24 h prior to challenge with Pichindé virus (PICV) was highly effective at protecting animals from mortality and preventing viral replication and liver-associated disease. A significant protective effect was still observed with a single dosing of DEF201 given two weeks prior to PICV challenge. DEF201 was also efficacious when administered as a treatment 24 to 48 h post-virus exposure. The protective effect of DEF201 was largely attributed to the expression of cIFN-α, as dosing with a control empty vector adenovirus did not protect hamsters from lethal PICV challenge. Effective countermeasures that are highly stable, easily administered, and elicit long lasting protective immunity are much needed for arena and other viral infections. The DEF201 technology has the potential to address all of these issues and may serve as a broad-spectrum antiviral to enhance host defense against a number of viral pathogens.